Resolutions and Decisions Adopted by the General Assembly During its Seventy-eight Session: Volume III - United Nations (United Nations, 2024)
This regular publication comprises the official record of all the resolutions and decisions adopted by the United Nations General Assembly during the course of its seventy-eight session. (Supplement No. 49, Volume. III)